Xenomic networks variability and adaptation traits in wood decaying fungi. Issue 3 (2nd January 2013) - Morel, Mélanie; Meux, Edgar; Mathieu, Yann; Thuillier, Anne; Chibani, Kamel; Harvengt, Luc; Jacquot, Jean‐Pierre; Gelhaye, Eric
Summary: Fungal degradation of wood is mainly restricted to basidiomycetes, these organisms having developed complex oxidative and hydrolytic enzymatic systems. Besides these systems, wood‐decaying fungi possess intracellular networks allowing them to deal with the myriad of potential toxic compounds resulting at least in part from wood degradation but also more generally from recalcitrant organic matter degradation. The members of the detoxification pathways constitute the xenome. Generally, they belong to multigenic families such as the cytochrome P450 monooxygenases and the glutathione transferases. Taking advantage of the recent release of numerous genomes of basidiomycetes, we show here that these multigenic families are extended and functionally related in wood‐decaying fungi. Furthermore, we postulate that these rapidly evolving multigenic families could reflect the adaptation of these fungi to the diversity of their substrate and provide keys to understand their ecology. This is of particular importance for white biotechnology, this xenome being a putative target for improving degradation properties of these fungi in biomass valorization purposes. Abstract : Cytochrome P450 monooxygenases and glutathione transferases are part of the xenome, responsible for degradation of complex molecules. In wood decaying fungi, these multigenic families are functionally related and evolve rapidly both at the genomic and functional level, reflecting adaptation of fungi to the substrate diversity and provide keys to understand their ecology.